Magnetotactic Bacteria as Potential Sources of Bioproducts - Ana Carolina V. Araujo; Fernanda Abreu; Karen Tavares Silva; Dennis A. Bazylinski; Ulysses Lins (Marine Drugs, 2015)
Magnetotactic bacteria (MTB) produce intracellular organelles called magnetosomes which are magnetic nanoparticles composed of magnetite (Fe3O4) or greigite (Fe3S4) enveloped by a lipid bilayer. The synthesis of a magnetosome is through a genetically controlled process in which the bacterium has control over the composition, direction of crystal growth, and the size and shape of the mineral crystal. As a result of this control, magnetosomes have narrow and uniform size ranges, relatively specific magnetic and crystalline properties, and an enveloping biological membrane. These features are not observed in magnetic particles produced abiotically and thus magnetosomes are of great interest in biotechnology. Most currently described MTB have been isolated from saline or brackish environments and the availability of their genomes has contributed to a better understanding and culturing of these fastidious microorganisms. Moreover, genome sequences have allowed researchers to study genes related to magnetosome production for the synthesis of magnetic particles for use in future commercial and medical applications. Here, we review the current information on the biology of MTB and apply, for the first time, a genome mining strategy on these microorganisms to search for secondary metabolite synthesis genes. More specifically, we discovered that the genome of the cultured MTB Magnetovibrio blakemorei, among other MTB, contains several metabolic pathways for the synthesis of secondary metabolites and other compounds, thereby raising the possibility of the co-production of new bioactive molecules along with magnetosomes by this species.